Evaluation of effectiveness parameters on gas dehydration plant - Nuramalina Munirah, Rosli (2013)
Natural gas in either from natural production or storage reservoirs contain water,which condensed and form solid gas hydrates that can cause trouble to the pipeline,increases the operating pressure and potential damage to the equipment.Thus dehydration of natural gas is important to ensure smooth operation of gas transmission line.This study focused on the dehydration by the absorption of liquid desiccant.The purpose of this study was to evaluate the effectiveness parameters used in Triethylene Glycol unit. Water need to be removed from the Natural Gas to meet a water dew point requirement of sale gas contract specification range from 32.8 to 117 kg/ 106 standard m3. The evaluation of effectiveness parameters on gas dehydration plant used Aspen HYSYS.Peng-Robinson Equation of State has been chosen because the process involved hydrocarbon and water.The simulation was carried out to identify the effect of the parameter of column operating pressure, gas flow rate, inlet gas temperature and number of theoretical stages of the absorber.The optimum conditions of gas dehydration was at 7000 kPa with 100 mmscfd gas flow rate at 30 oC and 8 column theoretical stages.